The anti-atherosclerotic effects of puerarin on induced-atherosclerosis in rabbits - Bao, Lidao; Zhang, Ying; Wei, Guomin; Wang, Yi; Ma, Ruilian; Cheng, Rui; Ren, Xianhua; Agula, B. (Biomedical papers, 2015)
Background: Cardiovascular disease is a major health issue worldwide, which has been well treated by the extracts of traditional herbs. Radix Puerariae, the dried root of the leguminous plant Pueraria lobata (Willd.) Ohwi, is a delicious vegetable in some southern provinces of China. Puerarin has also been widely used to treat human diseases, but few controlled studies are available.Aim: To determine the anti-atherosclerotic effects of puerarin on fat diet-induced atherosclerosis (AS) in rabbits.Methods: An AS model was established by feeding 60 rabbits a high-fat diet and randomly dividing them into 6 groups: (1) normal control, (2) a model group (3) the statin, simvastatin and groups (4), (5) and (6) received 3 different amounts of puerarin. The fasting sera of all animals were collected before and after 90 days treatment to determine the levels of total cholesterol (TC), triglyceride (TG), low density lipoprotein-cholesterol (LDL-C) and high density lipoprotein-cholesterol (HDL-C). The aortas were pathomorphologically examined. PCNA and PDGF-A protein levels were assessed by Western blot.Results: On the 90th day, the levels of TC, TG and LDL-C were significantly lower in high- and middle-dose puerarin groups and simvastatin group than in the model group (P<0.05), and the HDL-C level was higher. The percentages of plaque area to the total aortic area differed significantly for high- and middle-dose puerarin groups, simvastatin group and model group (P<0.05). Whole blood viscosity increased in the high-fat diet groups, while those in the treatment groups (except for the low-dose puerarin group) were significantly lower than those in the model group (P<0.05). PCNA and PDGF-A protein expression levels of rabbit aorta were low in the normal group. Protein expression levels in the groups fed the high-fat diet were significantly increased (P<0.05), but those in the high-dose puerarin group and simvastatin group were significantly decreased compared with the model group (P<0.05).Conclusions: Puerarin inhibits the formation and development of AS plaque and suppresses the migration and reproduction of vascular smooth muscle cells by decreasing PCNA and PDGF-A expressions in the rabbit. This is encouraging in terms of cardiovascular disease prevention/treatment.
Keywords: puerarin; rabbit; atherosclerosis; proliferation cell nuclear antigen; platelet-derived growth factor